Examining the Relation of Transformational Leadership in Clinical Engineering on the Performance of Medical Equipment: A Neural Network Approach - Waly, Mohamed Ibrahim (International Journal of Online and Biomedical Engineering (iJOE), 2024)
In the realm of healthcare administration, heightened expectations can lead to stress, therefore impacting working conditions. Specifically, studies on leadership styles have provided a valuable understanding of the factors that hinder performance, particularly in relation to the implementation of transactional leadership. Despite its crucial significance, there is a dearth of research on the management styles employed in clinical engineering. This study examines the impact of leadership styles on the functioning of medical equipment. We assess leadership styles and the performance of medical equipment from the perspective of end-users using a cross-sectional survey and questionnaires that consider many significant criteria. A neural network model is employed to classify the leadership styles exhibited by the Clinical Engineering Department (CED) and to analyze the correlation between these styles and the equipment’s performance. The results suggest a significant correlation between the leadership styles of those in charge of CED and the functioning of medical equipment. A strong and favorable correlation exists between transformative leadership and equipment performance (r = 0.856**, P = 0.000). The data suggests that transformative leadership is highly significant, with a mean score of 3.07 ± 0.817.